First-Pass Contrast-Enhanced MR Angiography in Evaluation of Treated Spinal Arteriovenous Fistulas: Is Catheter Angiography Necessary? - Mathur, S.; Symons, S.P.; Huynh, T.J.; Marotta, T.R.; Aviv, R.I.; Bharatha, A. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Catheter angiography is typically used for follow-up of treated spinal AVFs. The purpose of this study was to determine the diagnostic performance and utility of first-pass contrast-enhanced MRA in the posttreatment evaluation of spinal AVFs compared with DSA.MATERIALS AND METHODS: A retrospective review was performed of all patients at our tertiary referral hospital (from January 2000 to April 2015) who underwent spine MR imaging, first-pass contrast-enhanced MRA, and DSA after surgical and/or endovascular treatment of a spinal AVF. Presence of recurrent or residual fistula on MRA, including vertebral level of the recurrent/residual fistula, was evaluated by 2 experienced neuroradiologists blinded to DSA findings. Posttreatment conventional MR imaging findings were also evaluated, including presence of intramedullary T2 hyperintensity, perimedullary serpentine flow voids, and cord enhancement. The performance of MRA and MR imaging findings for diagnosis of recurrent/residual fistula was determined by using DSA as the criterion standard.RESULTS: In total, 28 posttreatment paired MR imaging/MRA and DSA studies were evaluated in 22 patients with prior spinal AVF and 1 patient with intracranial AVF with prior cervical perimedullary venous drainage. Six image sets of 5 patients demonstrated recurrent/residual disease at DSA. MRA correctly identified all cases with recurrent/residual disease with 1 false-positive (sensitivity, 100%; specificity 95%; P < .001), with correct localization in all cases without interobserver disagreement. Conventional MR imaging parameters were not significantly associated with recurrent/residual spinal AVF.CONCLUSIONS: First-pass MRA demonstrates high sensitivity and specificity for identifying recurrent/residual spinal AVFs and may potentially substitute for DSA in the posttreatment follow-up of patients with spinal AVFs.SAVFspinal AVF